AWARENESS AND KNOWLEDGE OF ORAL CANCER IN URBAN PUNE POPULATION: A SURVEY BASED QUESTIONNAIRE STUDY - SUDHIR, SHINDE; Ameya R, Sangle; Abhinav, Shrivasatav; Juthikaa., Deherkar (International Journal of Clinical and Biomedical Research, 2016)
A self-administered survey based questionnaire study about oral carcinoma conducted at Bharati hospital, Pune. Aims: To assess the awareness and knowledge about oral malignancy, to assess the knowledge about risk factors related to oral malignancy and to assess the awareness about signs/symptoms of oral cancer in urban Pune. A self designed questionnaire-based survey was conducted at the OPD of a tertiary care institute. Materials and Methods: A self administered questionnaire-based survey. Time period: two months Study Area: OPD of a tertiary care hospital in Pune. Total Participants: 500 persons. Statistical analysis used: The collected data were analyzed using SPSS software to assess and associate oral cancer awareness. Results: The general awareness, knowledge of signs and risk factors of oral cancer were found to be proportionate to the literacy level with the highest rate of awareness being among health-care workers and post-graduates and lowest among illiterates. It was also observed that on most of these dimensions the younger age groups (<30 years) were significantly more knowledgeable. Conclusion: The awareness of oral cancer in the population of Pune was not satisfactory, pointing to a need for further dissemination of information on this issue. This is especially important for the youngsters, as this may possibly help them keep away from indulgence in any form.